Qualitative Descriptive Study on Verbal Communication of Indonesian Women in ‘Pengajian and Arisan’ Community in Brisbane, Australia - Prasanti, D; Indriani, S S (KnE Social Sciences, 2018)
Indonesian women living in Australia have a different way in using their verbal communication than the Australians. They also perform activities that consist of cultural traditions of Indonesia, such as Pengajian (Quran reciting) and Arisan, but the fact that they live in Australia not in Indonesia can create a new blend of two cultures. The relationship between culture and communication is a mutual lone, both complete each other, neither can be separated because they both affect each other. What is communicated between them through symbolic interaction creates a culture, and the culture will influence back the way they communicate. This research problem focused on the following questions: How is the verbal communication process of Indonesian women in the Pengajian and Arisan Community in Brisbane, Australia? The research conducted a qualitative approach with descriptive methods. The data collection techniques included interviews, observation and documentation study. The results from this study shows that when the Indonesian women gathered, they established a new pattern language/paralinguistic among the Indonesian women, while the topics that were usually discussed were problems concerning: (1) food and Indonesian cuisine, (2) the problems that exist in Indonesia and (3) gossiping about others. Keywords: verbal communication, women Indonesia, Australia